MODEL OF CHANGE MANAGEMENT PERFORMANCE IN CITRARAYA PARISH THROUGH THE LEADERSHIP ROLE OF THE PARISH PRIESTS - Matius Bili; Mercurius Broto Legowo (Universitas Pelita Harapan, 2025)
Change management in religious organizations, such as parishes, requires an effective management model so that it can run well and sustainably. The lack of consideration of personal quality factors and leadership of parish priests is a major problem in realizing better change management performance. This study is intended to initiate a change management performance model in Citra Raya Parish through the leadership role of the parish priest. This study uses an empirical research method with a quantitative approach, with a case study in Citra Raya Parish. Valid data was collected from 100 parishioners through an online empirical survey, using a purposive random sampling technique. The results of the study show that the effectiveness of change management performance in the parish environment was influenced by the role of the pastor's leadership style and the personal qualities he possesses. Theoretically, these results contribute significantly to the existing literature, in line with the understanding that good leadership and personal qualities impact the ability to overcome management changes in an organization in this case study in a religious organization. The performance model of change management in Citra Raya Parish produced in this study has significant benefits and can contribute to being a reference for other churches in managing change more systematically and sustainably.